2021
DOI: 10.1016/j.arr.2021.101344
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in muscle architecture and metabolism in humans: The likely contribution of physical inactivity to age-related functional decline

Abstract: Highlights Ageing is associated with declines in muscle mass, quality and insulin sensitivity. These features of ageing quickly manifest in young exposed to physical inactivity. The cellular mechanisms of inactivity-driven muscle dysregulation are unclear. The precise contribution of inactivity to muscle decline with age is unknown. Muscle ageing caused by lifestyle factors may be at least partly reversible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 79 publications
0
30
0
2
Order By: Relevance
“…Muscular strength was included in this study to verify the impact of social isolation on the physical health of elderly. It is known that restrictions to the practice of phys-ical activity tend to affect muscular components and intensify physiological changes of aging [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Muscular strength was included in this study to verify the impact of social isolation on the physical health of elderly. It is known that restrictions to the practice of phys-ical activity tend to affect muscular components and intensify physiological changes of aging [25].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…is outcome was congruent with previous studies [21][22][23], in which older adults showed a more sedentary lifestyle. Age-related changes in muscle architecture and metabolism [39] may lead to physical inactivity, which is a concern with the aging society and the burden of KOA in Taiwan. Further studies are needed to develop an effective PA program to improve health and avoid adverse outcomes for older people, especially those with KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Within sedentary individuals, YC had a better performance than SC probably attributable to a significantly higher muscle power, suggesting again that aging negatively affects muscle power [ 27 ]. In conclusion, both aging and sedentarism result in a decreased muscle power in the M1LH test, but lifelong training could be associated to a counterbalance of the effects of aging [ 28 , 29 , 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%